Age and Parity with Baby Blues Syndrome in Postpartum Mothers at the Teling Community Health Center, Manado City - Massa, Kartini; Kaghoo, Noifke; Ali, Stendy (Sarana Ilmu Indonesia (salnesia), 2025)
The first week for postpartum mothers is a period of adjustment to the role and responsibilities of mothers after giving birth. Mothers who are unable to adapt well during the postpartum period are susceptible to experiencing psychological disorders, one of which is baby blues syndrome. This study aimed to determine the relationship between age and parity with baby blues syndrome at the Teling Atas Community Health Center in Manado. The research method was observational analytic, with a cross-sectional approach. Samples were taken by accidental sampling of a sample of 60 postnatal mothers who met the inclusion criteria. Data were collected using the Edinburgh Postnatal Depression Scale/EPDS questionnaire and data analysis using Chi-square statistical tests. The results of the study showed that the majority of mothers were 20-35 years old, as many as 55 (91,7%), the highest parity was primipara, as many as 38 people (63,3%). There was a relationship between age (p-value<0,005 and parity (p-value<0,001) with baby blues syndrome at the Teling Atas Manado Health Center. It is recommended that health workers be more active in increasing counseling for pregnant women in preparation for becoming mothers so that they can adapt well after giving birth.